Effects of diet supplementation with rumen-protected betaine on carcass characteristics and fat deposition in growing lambs. (August 2020) - Dong, Li; Jin, Yaqian; Cui, Huihui; Yu, Lihuai; Luo, Yang; Wang, Shunan; Wang, Hongrong
Abstract: This study evaluated the effects of dietary rumen-protected betaine (RPB ) supplementation on the fat deposition of lambs. Sixty Hu sheep were randomly divided into 5 groups. The lambs were fed a control diet (CON ) or diets supplemented with 1.1 g/d unprotected betaine (UPB ), 1.1 g/d RPB, 2.2 g/d RPB or 3.3 g/d RPB for 70 days. Compared with UPB, the abdominal fat in 2.2 g/d RPB supplemented group was decreased ( P  < .05). Compared with CON and UPB, the fat contents in longissimus dorsi (LD ) of RPB treatments were increased ( P  < .01). With increasing of RPB levels, the fat content in the LD was quadratically increased ( P  < .05). Compared with CON, genes expression of PI3K, mTOR and S6K1 in the LD of RPB treatments were up-regulated ( P  < .05). In conclusion, RPB supplementation decreased the abdominal fat in lambs but increased the fat content in lamb meat, and this effect might be regulated by mTOR signaling.